Investigation of the Factors Affecting Technical and Economic Indicators of Thermal Insulation of External Walls of Buildings - Yulyia, Kolomiiets; Dzhalalov Mykhayl, Dzhalalov; Tamara, Kulishenko (International Journal of Engineering and Technology, 2018)
The technology of insulation of enclosing constructions of buildings and constructions is characterized. The method of technological design on the basis of integrated production of technological processes, estimation and influence of organizational and technological reliability of building production depending on methods, technologies and constructive decisions is given.The data collection for the energy certificate of the building is shown. Energy certificate of the building is a document containing the geometrical, energy and heat engineering characteristics of the building being designed or operated, as well as the characteristics of the heat insulation. This document also establishes the compliance of the building with the requirements of regulatory documents. The energy passport of the building is not intended to be used to make payments for utility or other services provided to homeowners, tenants and apartment owners.Energy assessment of the building - energy efficiency of buildings should be determined on the basis of estimated or actual annual energy consumption necessary to meet various needs associated with its typical use in the building. These needs should include the energy consumption for heating and cooling to maintain the desired temperature, as well as hot water supply.Â Â